2003
DOI: 10.1590/s0100-879x2003000500001
|View full text |Cite
|
Sign up to set email alerts
|

Protein defects in neuromuscular diseases

Abstract: Muscular dystrophies are a heterogeneous group of genetically determined progressive disorders of the muscle with a primary or predominant involvement of the pelvic or shoulder girdle musculature. The clinical course is highly variable, ranging from severe congenital forms with rapid progression to milder forms with later onset and a slower course. In recent years, several proteins from the sarcolemmal muscle membrane (dystrophin, sarcoglycans, dysferlin, caveolin-3), from the extracellular matrix (a2-laminin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 54 publications
1
16
0
15
Order By: Relevance
“…The identification and classification of these three phenotypes may reflect important inter-and intra-familiar clinical variability, which is seen in DMD patients and which cannot be attributed to genetic factors (Vainzof and Zatz, 2003), but a correlation between the amount of dystrophin and the severity of the phenotype has been suggested by the cited authors. Sifringer et al (2004) suggested that an increase in some proteins such as casein kinase I, dynactin 3 light chain and the core-binding factor beta, which are involved in the regulation of the cell cycle, may be related to a milder phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and classification of these three phenotypes may reflect important inter-and intra-familiar clinical variability, which is seen in DMD patients and which cannot be attributed to genetic factors (Vainzof and Zatz, 2003), but a correlation between the amount of dystrophin and the severity of the phenotype has been suggested by the cited authors. Sifringer et al (2004) suggested that an increase in some proteins such as casein kinase I, dynactin 3 light chain and the core-binding factor beta, which are involved in the regulation of the cell cycle, may be related to a milder phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may be able to walk throughout their lives. A patient is classified as having DMD when wheelchair-dependent before the age of 13, and as having BMD when able to walk beyond the age of 16 (Vainzof and Zatz, 2003). However, a recent clinical casebook described a boy without any signs of DMD (Dubowitz, 2006) but with confirmation of molecular findings.…”
Section: Discussionmentioning
confidence: 99%
“…-In the cited review from Vainzof and Zatz (2003), there are wrong interpretations. DMD patients DO NOT show important inter-and intrafamiliar clinical variability, as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…DMD patients DO NOT show important inter-and intrafamiliar clinical variability, as mentioned above. In this review, Vainzof and Zatz (2003) commented about clinical inter-and intrafamilial variability in several other genetic disorders, including SOME other forms of muscular dystrophies, and highlighted the role of possible modifying genes and protein interactions in determining this phenotypic variability;…”
Section: Discussionmentioning
confidence: 99%
“…After this phase, it follows a decline of the pulmonary function [13], and the respiratory failure is the cause of death in about 80% of the patients [14][15]. Survival goes until the third decade of life (about 25 years of age), mainly due to cardiac or respiratory failure [16]. Ventilation with the help of a non-invasive ventilatory support (NIV) minimizes the progression of the ventilatory insufficiency, improving therefore, the quality of life and life expectancy [17].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%